Character education of elementary school students on online learning - Al Mahabbah Havi, Shaden; Srinana Wardani , Imas; Irianto , Apri (Universitas Nusantara PGRI Kediri, 2022)
This research is motivated by a change in the learning system to be online and has an impact on the application of character education to elementary school students. This is because the implementation of character education that was previously exemplified directly, but the result of these changes cannot be implemented and creates obstacles and strategies carried out by teachers and parents. The purpose of this study was to identify and identify the strategies and constraints experienced during the implementation of character education learning in online learning during the Covid 19 pandemic. The research method used was descriptive qualitative research, data collection was carried out through interviews with informants in the study. That is the way teachers and parents, parents, about what processes and constraints are experienced during online learning. The results of this study are in the form of strategies that have been implemented by schools and parents to deal with obstacles to online character learning, including the implementation of character education learning through habituation at home activities that reflect discipline and responsibility.